THE APPLICATION OF QUANTUM TEACHINGÂ MODEL WITH PUZZLE MEDIA IN IMPROVING WRITING SKILLSÂ AT THE FOURTH GRADE STUDENTSÂ OF SDN 6 PANJERÂ IN THE ACADEMIC YEAR OF 2014/2015 - Retraningtyas, Septiana (KALAM CENDEKIA PGSD KEBUMEN, 2015)
Abstract: The Application of Quantum Teaching Model with Puzzle Media in Improving Writing Skills at The Fourth Grade Students of SDN 6 Panjer in the Academic Year of 2014/2015. The purpose of research to describe the aplication of Quantum Teaching model with puzzle media, to improve the essay writing skills, and to describe the problems and solutions in the aplication of Quantum Teaching model with puzzle media. This research is Collaborative Classroom Action Research (CAR) which carried out in three cycles. The subject of the research was 33 students of the fourth grade students of SDN 6 Panjer, consisting of 22 male and 11 female students. The results showed The Application of Quantum Teaching Model with Puzzle Media can improve essay writing skills at the fourth grade students of SDN 6 Panjer in the academic year of 2014/2015. Keyword: Quantum Teaching, puzzle media, writing skills Abstrak: Penggunaan Model Quantum Teaching dengan Media Puzzle dalam Peningkatan Keterampilan Menulis Karangan bagi Siswa Kelas IV SDN 6 Panjer Tahun Ajaran 2014/205. Tujuan penelitian ini adalah mendeskripsikan langkah-langkah penggunaan model Quantum Teaching dengan media puzzle, meningkatkan keterampilan menulis karangan, serta mendeskripsikan kendala dan solusi penggunaan model Quantum Teaching dengan media puzzle. Penelitian ini merupakan Penelitian Tindakan Kelas (PTK) kolaborasi yang dilaksanakan dalam 3 siklus. Subjek penelitian ini siswa kelas IV SDN 6 Panjer yang berjumlah 33 siswa terdiri dari 22 laki-laki dan 11 perempuan. Simpulan penelitian ini adalah penggunaan model Quantum Teaching dengan media puzzle dapat meningkatkan keterampilan menulis karangan bagi siswa kelas IV SDN 6 Panjer tahun ajaran 2014/2015. Kata Kunci: Quantum Teaching, media puzzle, keterampilan menulis